GENERATING ASPECT-ORIENTED VERB PARADIGMS IN MACEDONIAN (Philological Studies, 2019)
The paper outlines the theoretical background behind a recent online Macedonian aspectual conjugator, located at asp.vigna.mk, by describing the current state of the Macedonian verb system from the perspective of traditional aspect theory. The research on and development of such an online reference resource has been motivated by the lack of descriptions of formal aspect-related problems in textbooks and grammars on contemporary Macedonian.
Keywords: computational linguistics, aspect-oriented conjugation, verbs, aspect, online conjugator